Hormonal synchrony in older couples' everyday life: the role of situational stressors and buffers - Hopf, Dora; Aguilar-Raab, Corina; Gödde, Johanna Ulrike; Schneider, Ekaterina; Ditzen, Beate; Eckstein, Monika (Hormones and behavior, 2025)
Synchrony in physiology in romantic couples has been suggested to be a result of joint interaction and co-regulation of stress and affect. However, it is subject of debate whether synchrony in endocrine levels - especially in oxytocin - is generally beneficial or if a reciprocal transmission of stress may even be stress-increasing. The aim of this study was to investigate hormonal synchrony in older couples in relation to situational mindfulness, relationship conflict (quarreling), as well as situational resilience and subjective stress levels. A total of N = 26 individuals (i.e., N = 13 couples) aged between 52 and 75 years provided saliva samples and self-report measures 12 times over the course of 2 days (312 measures in total). Superior to randomly scrambled dyads, multilevel models predicted cortisol, alpha-amylase, and oxytocin levels from one partner for the other. Synchrony was higher at times of high levels of quarreling but mitigated in moments of high mindfulness. Moreover, oxytocin synchrony was reduced in couples exerting higher average levels of stress. We interpret this finding as buffering personal factors to protect against the transmission of dyadic stress. To draw implications for clinical interventions to promote these factors and given the preliminary character of the sample and the effects, future studies need to systematically expand this field of research and application.